Use of virtual reality glasses during sitting position in patients with COVID-19 admittes to an Intensive Care Unit: Randomized clinical trial (Research, Society and Development, 2024)
Introduction: Prolonged hospitalization due to COVID-19 generates functional alterations, of which early mobilization with the aid of Virtual Reality (VR) recovers and alleviates these conditions. Objective: To evaluate the effects of using immersive VR on the level of pain, length of stay in bedside sitting position and mobility of patients diagnosed with COVID-19, hospitalized in Intensive Care Units (ICU). Methods: This study was carried out with patients diagnosed with COVID-19 and admitted to the adult ICUs of the Campos Gerais Regional University Hospital of the State University of Ponta Grossa. The patients were divided into two groups: virtual reality - sitting position with the virtual reality glasses, and the bedside sitting position group - without the glasses. Pain and mobility were measured before and after sitting, as well as the time spent in this position. Results: 40 patients were included, 20 in the bedside sitting position group with a mean age of 53.55 years and 20 in the virtual reality group with a mean age of 50.7 years. Conclusion: The use of virtual reality in physiotherapy for ICU patients, in a single session, is safe and provides more time in the sitting position, but does not affect mobility and pain control.